Blood—Brain Barrier Breakdown Involves Four Distinct Stages of Vascular Damage in Various Models of Experimental Focal Cerebral Ischemia. Issue 2 (February 2015) - Krueger, Martin; Bechmann, Ingo; Immig, Kerstin; Reichenbach, Andreas; Härtig, Wolfgang; Michalski, Dominik
Ischemic stroke not only impairs neuronal function but also affects the cerebral vasculature as indicated by loss of blood—brain barrier (BBB) integrity. Therefore, therapeutical recanalization includes an enhanced risk for hemorrhagic transformation and bleeding, traditionally attributed to a 'reperfusion injury'. To investigate the mechanisms underlying ischemia-/reperfusion-related BBB opening, we applied multiple immunofluorescence labeling and electron microscopy in a rat model of thromboembolic stroke as well as mouse models of permanent and transient focal cerebral ischemia. In these models, areas exhibiting BBB breakdown were identified by extravasation of intravenously administered fluorescein isothiocyanate (FITC)-albumin. After 24 hours, expression of markers for tight and adherens junctions in areas of FITC-albumin leakage consistently remained unaltered in the applied models. However, lectin staining with isolectin B4 indicated structural alterations in the endothelium, which were confirmed by electron microscopy. While ultrastructural alterations in endothelial cells did not differ between the applied models including the reperfusion scenario, we regularly identified vascular alterations, which we propose to reflect four distinct stages of BBB breakdown with ultimate loss of endothelial cells. Therefore, our data strongly suggest that ischemia-related BBB failure is predominantly caused by endothelial degeneration. Thus, protecting endothelial cells may represent a promising therapeutical approach in addition to the established recanalizing strategies.